2010
DOI: 10.1038/hdy.2010.42
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaco-epigenomics: discovering therapeutic approaches and biomarkers for cancer therapy

Abstract: An important feature of cancer is dysregulation of gene activity and gene expression, which is driven by a combination of acquired genetic and epigenetic alterations. Here, we will highlight how insights into the epigenetic processes underpinning tumor biology have led to the emerging field of cancer pharmaco-epigenomics. First, we will discuss how interference with the epigenetic machinery in cancer is leading to novel promising therapies, with several DNA methyltransferase and histone deacetylase inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 86 publications
0
26
0
Order By: Relevance
“…Several review articles recently described rationales, targets, new drugs, approaches, novel compounds and methodologies [12,17,18,20,[22][23][24][25][35][36][37][38][39][40][41]65,[226][227][228][229]. A large amount of these insightful articles have been dedicated to well established drug targets such as the histone deacetylases (HDACs) and DNA methyltransferases, and to the status of the development of small-molecule compounds [25,31,45,55,230,231].…”
Section: Structural Data Of Epigenetic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several review articles recently described rationales, targets, new drugs, approaches, novel compounds and methodologies [12,17,18,20,[22][23][24][25][35][36][37][38][39][40][41]65,[226][227][228][229]. A large amount of these insightful articles have been dedicated to well established drug targets such as the histone deacetylases (HDACs) and DNA methyltransferases, and to the status of the development of small-molecule compounds [25,31,45,55,230,231].…”
Section: Structural Data Of Epigenetic Targetsmentioning
confidence: 99%
“…+39 051 2094004; Fax: +39 051 2094746; Email: alberto.delrio@gmail.com # These authors contributed equally to this work and regulation of the immune system [29,30], epigenetic changes are at the limelight of cancer research. Many studies have found that alterations in the epigenetic code may contribute to the onset of growth and progression of a variety of cancers [20,21,23,[31][32][33][34][35][36][37][38][39][40][41]. For this reason, these enzymes are attractive therapeutic targets for the development of new cancer therapies [3,[42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the functional characterization of the variety of epigenetic modifications at specific loci could provide insight into the function of these modifications in normal development and in subsequent transition to disease states. These studies could ultimately lead to the future development of more effective epigenetic-based therapies, although treatment with these classes of drugs should be carefully examined to determine whether the therapeutic benefits outweigh the potential adverse effects [163, 164]. …”
Section: Discussionmentioning
confidence: 99%
“…In cancer, it has been established that certain tumor types respond well to DNMT and histone deacetylase (HDAC) inhibitor treatments, with the best clinical efficacy seen in hematologic malignancies [39]. Histone methyltransferase and demethylase inhibitors are also proposed as treatments of cancer, as these enzymes are involved in tumorigenesis and tumor progression [40].…”
Section: Drugs and Nutrition With Epigenetic Effectsmentioning
confidence: 99%
“…Therefore, epigenetic assays should be incorporated into the safety assessment of pharmaceutical drugs [46]. The impact of this new approach, “pharmacoepigeneomics”, may be greater than that of pharmacogenomics [39,46]. …”
Section: Drugs and Nutrition With Epigenetic Effectsmentioning
confidence: 99%